Measuring the subprime crisis contagion: Evidence of change point analysis of copula functions - Ye, Wuyi; Liu, Xiaoquan; Miao, Baiqi (European journal of operational research, 2012)
► We use the change point testing method to determine the existence of financial contagion. ► We adopt copula upper tail dependence coefficient as measure of the degree of contagion. ► We investigate contagion during the credit crunch between the US and five Asian markets. In this paper, we first determine the existence of structural changes in the dependence between time series of equity index returns of two markets using the change point testing method. The method is based on Archimedean copula functions, which are able to comprehensively describe dependence characteristics of random variables. The degree of financial contagion between markets is subsequently estimated using the tail dependence coefficient of copula functions before and after the change point. We empirically test our method by investigating financial contagion during the subprime crisis between the US S&P 500 index and five Asian markets, namely China, Japan, Korea, Hong Kong and Taiwan. Our results show that a statistically significant change point exists in the dependence between the US market and all Asian stock markets except Taiwan. The upper tail dependence is larger after the time of change, implying the existence of contagion during the banking crisis between the US and the Asian economies. The degree of financial contagion is also estimated and found to be consistent with market events and media reports during that period.